Study of serum angiotensin converting enzyme levels in pemphigus vulgaris - Anand Kumar, V.; Vijaya Shree, J. (International Journal of Research in Dermatology, 2018)
Background: This study aimed to evaluate the serum angiotensin converting enzyme (ACE) levels in patients with pemphigus vulgaris compared with healthy volunteers. Methods: In this study, 40 patients were selected in the study group with pemphigus vulgaris and 40 patients were selected in the control group i.e. healthy group. Serum ACE levels were determined by spectrophotometric method. Results: The mean ACE levels in study group and control group were 26.98±15.87 and 32.57±20.98 respectively. There was no statistically significant difference between both the groups (p=0.11). The mean ACE levels were 26.25±12.36 and 26.14±13.89 in females and males respectively in the study group which showed no significant difference (p=0.95). In the control group, the mean ACE levels were 26.22±19.77 and 38.54±11.11 in females and males respectively which showed a statistically significant difference (p=0.04). The mean ACE levels were higher in healthy males when compared to the males in the study group. The mean serum levels in females of both the groups were almost same. Conclusions: The serum ACE level was considerably lower in male study group i.e. pemphigus vulgaris patients compared with male control group i.e. healthy group, despite lack of any significant difference of serum ACE level between pemphigus and control group. Hence, ACE might have some relation with pemphigus vulgaris especially in male patients.